2022
DOI: 10.52711/0974-360x.2022.00066
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical profiling of hot and cold alcoholic extract from Spirulina platensis alga and Comparison between two extracts against multidrug -resistant bacteria

Abstract: Background: Bacterial infections are one of the prominent problems causing death, health troubles and physical disabilities all over the world. Objective: This study was aimed to compare between hot and cold alcoholic extract of Spirulina platensis. Materials and Methods: in regards to antibacterial efficacy against several multidrug-resistant Gram-positive and Gram-negative bacteria, Spirulina was isolated from a freshwater station located in Baghdad, then identified in consideration to molecular analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…This suggests that other organic solvents extracted from S. platensis have the potential to be studied and further used as antimicrobial agents. The results of a study concluded that the ethyl-acetate crude extract of S.platensis is effective against S.aureus but has no effect on E.coli, this disagrees with our study due to the fact that ethyl-acetate extract had no significant effect on either S.aureus or E.coli (Fayyad et al, 2022). Moreover, the inhibitory activity is influenced by the type of algae the effectiveness of the extraction technique, and the active intergradient (Lechuga Morente, 2021).…”
Section: Antimicrobial Activitycontrasting
confidence: 99%
“…This suggests that other organic solvents extracted from S. platensis have the potential to be studied and further used as antimicrobial agents. The results of a study concluded that the ethyl-acetate crude extract of S.platensis is effective against S.aureus but has no effect on E.coli, this disagrees with our study due to the fact that ethyl-acetate extract had no significant effect on either S.aureus or E.coli (Fayyad et al, 2022). Moreover, the inhibitory activity is influenced by the type of algae the effectiveness of the extraction technique, and the active intergradient (Lechuga Morente, 2021).…”
Section: Antimicrobial Activitycontrasting
confidence: 99%
“…After being finished, the extract was filtered, condensed with a rotary evaporator at a regulated temperature and lowered pressure of 50°C-60°C (100 mg/mL of concentration), and then stored at room temperature for later use. 13 Methanolic extracts of C. goensis and C. glomerata were subjected to GC-MS analysis.…”
Section: Extract Preparationmentioning
confidence: 99%
“…Alcoholic extract was made using soxhelet method of extraction [10]. The hexane used in this method dry the algal material into a powder.…”
Section: Preparation Of Alcoholic Extractmentioning
confidence: 99%